2020
DOI: 10.1103/physrevd.101.064045
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and phase transition of a Gauss-Bonnet black hole in a cavity

Abstract: Considering a canonical ensemble, in which the temperature and the charge on a wall of the cavity are fixed, we investigate the thermodynamics of a D-dimensional Gauss-Bonnet black hole in a finite spherical cavity. Moreover, it shows that the first law of thermodynamics is still satisfied. We then discuss the phase structure and transition in both five and six dimensions. Specifically, we show that there always exist two regions in the parameter space. In one region, the system possesses one single phase. How… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…This four-dimensional Einstein-Gauss-Bonnet gravity theory was further improved and a consistent theory was proposed in [58]. The generalization to other black hole solutions are referred to [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78].…”
Section: (): V-volmentioning
confidence: 99%
“…This four-dimensional Einstein-Gauss-Bonnet gravity theory was further improved and a consistent theory was proposed in [58]. The generalization to other black hole solutions are referred to [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78].…”
Section: (): V-volmentioning
confidence: 99%
“…In addition, properties of boson stars and hairy black holes in a cavity were investigated [47][48][49][50][51][52][53][54], which were shown to closely resemble those of holographic superconductors in the AdS gravity. Lately, it was discovered that Gauss-Bonnet black holes in a cavity have quite similar phase structure and transitions to the AdS counterparts [55]. These observations lend support to the analogy between black holes in a cavity and AdS black holes.…”
Section: Introductionmentioning
confidence: 76%
“…Recently, it is found that the resemblance still exist in the extended phase space [56]. And it was discovered that Gauss-Bonnet black holes in a cavity also have quite similar phase structure and transitions to the AdS counterparts [57]. However, it is shown that the phase structure of Born-Infeld black holes enclosed in a cavity has dissimilarities from that of Born-Infeld-AdS black holes [58,59].…”
Section: Introductionmentioning
confidence: 99%